Kekuatan Mengikat dan Alasan Para Pihak Menggunakan Suatu Bentuk Perjanjian Dalam Mengawali Hubungan Kerja di Kota Kupang - Lay Hire Wake, Raynaldi; Hedewata, Agustinus; Jacob, Yossie M Y (Artemis Law Journal, 2024)
The employment agreement, whether in written or oral form, holds significant benefits for the parties involved. This should be recognized because a well-made and adhered-to-employment agreement can create a peaceful work environment, guaranteeing rights and obligations for both workers and employers. Consequently, the company's productivity increases, and it can further open up new job opportunities. From the above description, the main issues are as follows: (1) What is the binding force and legal consequences of an employment agreement in terms of its form in the employment relationship in Kupang city? (2) Why do the parties use a particular form of agreement in the employment relationship in Kupang city? The purpose of this study is to determine the binding force and legal consequences of an employment agreement in terms of its form in the employment relationship in Kupang City. To find out the reasons why the parties use a particular form of agreement in the employment relationship in Kupang City. The research results prove that the binding force of an employment agreement in initiating an employment relationship in Kupang city is no different between oral and written agreements, as long as the agreement made complies with the legal requirements of a valid agreement as emphasized in Article 1230 of the Civil Code. The legal consequences of using both forms of employment agreements are equally binding on the parties according to the agreement's content. The issue arises when there is a conflict of interest between the parties; oral agreements will have a negative legal consequence in terms of proof, whereas written agreements can ensure legal certainty from the time the agreement is made until its termination. On the other hand, the reason the parties choose a written agreement to initiate an employment relationship in Kupang City is that a written agreement provides more certainty for the parties, whereas oral agreements are chosen more for practical reasons, saving time and costs. In general, this paper concludes that the binding force, legal consequences, and any form of employment agreement are the same as long as the parties are honest, especially during conflicts. The parties' choice of a particular form of agreement also has logical, practical, and legal certainty reasons.